Strengthening Inclusive Businesses for Disability Communities: Digital Marketing and Legality of Red Ginger Powder Products - Dini Selasi; Cory Vidiati; Ahmad Munajim; Fadli Firdaus Kanapi; Yayuk Sri Rahayu (Universitas Nurul Jadid, 2026)
Limited access to marketing, business legality, and digital technology often hinders the economic participation of persons with disabilities, including the Village Disabled Community (KDD) in Lemahabang Village, Cirebon Regency, which produces red ginger powder drinks. This community service aims to strengthen the inclusive business capacity of KDD through digital marketing development and regulatory compliance in order to increase product credibility and market reach. The program applied the Asset-Based Community Development (ABCD) approach through asset identification, participatory discussions and training, asset-based program development, program implementation, and monitoring and evaluation. Data were collected through observation, interviews, documentation, and focus group discussions, validated using triangulation techniques, and analyzed using SWOT analysis. The results indicate measurable improvements in business capacity. First, KDD successfully obtained business legality through the Business Identification Number (NIB) and initiated the process of P-IRT and halal certification to ensure product safety and consumer trust. Second, digital marketing strategies were implemented through social media promotion and improved inclusive product packaging, enabling broader market exposure. Third, collaboration with community stakeholders strengthened social entrepreneurship values and expanded marketing networks. These achievements demonstrate that strengthening legality, digital marketing capacity, and community collaboration can enhance the economic participation and confidence of persons with disabilities while improving the sustainability of red ginger product businesses.